Experimental Assessment of the Performance and Fine Particulate Matter Emissions of a LPG-Diesel Dual-Fuel Compression Ignition Engine - Eliezer Toledo; Fabián Guerrero; German Amador; Mario Toledo (Energies, 2022)
The present work is focused on the assessment of the performance and fine particulate matter emissions (PM2.5) of a turbocharged four-cylinder direct injection diesel engine operating under dual-fuel mode with Liquefied Petroleum Gas (LPG). For load levels of 30%, 60% and 100%, measurements were taken, keeping the engine speed constant at 2200, 2500 and 3200 rpm, while the engine knock detonation was detected through a non-invasive internal system. According to experimental measurements, the abnormal knock combustion occurred at full load operation with a maximum LPG energy fraction of ~60%. The brake fuel conversion efficiency increased by 2.6% with an LPG energy fraction of 10%, where a fuel saving of 11.9% was achieved with respect to the diesel-only operation. The reduction of diesel consumption was around 50% with respect to 100% diesel operation at full load operations, where the highest brake fuel conversion efficiency was achieved. The brake fuel conversion efficiency decreased as LPG addition increased for all the engine loads. Regarding emissions, PM2.5 decreased with the addition of LPG. However, HC and CO emissions increased as LPG injection was higher. NOx emissions and exhaust gas temperatures were reduced for operation with higher LPG fractions, except for full load levels at 2200 and 2500 rpm.